Women in academia and equality law : aiming high–falling short? : Denmark, France, Germany, Hungary, Italy, the Netherlands, Sweden, United Kingdom /: aiming high–falling short? : Denmark, France, Germany, Hungary, Italy, the Netherlands, Sweden, United Kingdom. (2006) - Unknown
No abstract available